Use of two dimensional electrical resistivity tomography (2D- ERT) synthetic modelling to detect collapse masses - Thapa, Dilli Ram (Journal of Nepal Geological Society, 2020)
The presence of collapse masses in the subsurface causes severe problems in the geotechnical design activities. In this study, two dimensional Electrical Resistivity Tomography (2D-ERT) synthetic modelling techniques were used to detect collapse masses commonly found in the river bank. Two dimensional (2D) resistivity models are first created utilizing prior information of collapsed masses in the river bank and afterward inverted to reconstruct the resistivity distribution in the subsurface. The resulting two dimensional models exhibits that collapsed masses can be better detected particularly at low resistivity noise level (2%) than the high noise levels (5% and 10%). The models are particularly very useful prior to executing the field investigations in the river bank sites and furnish the subsurface geology as well as the successful interpretation of the results withconfidence.